S-phase fraction and pro-inflammatory cytokine expressions in acute lymphoblastic leukaemia - Abdullah, Maha; Cheong, Soon Keng; Leong , Chooi Fun; Seow, Heng Fong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Despite much progress in treatment strategies, long term survival of adult ALL is still inferior to that in children. The underlying mechanisms for these differences are largely unknown. Intensification of contemporary therapy has also resulted in many children being over-treated. The action of chemotherapeutic drugs used in the treatment al ALL includes cell cycle dependent agents which are effective on cells that are proliferating. Cell proliferation in haemopoietic cells in controlled by cytikines. Thus, we proposed to study the cell cycle profile of ALL cases and also expression of cytokines to determine their role in affecting treatment outcome in the different age groups. Methods: We determined the S-phase fraction from the cell cycle profile by flowcytometry and tested expressions of cytokine IL-1β, IL-18, IFN-μ, TNF-α and GM-CSF using RT-PCR in de novo ALL cases. Results: We found a significantly higher S-phase fraction in smaples from children 2-10 years old compared to the older age group (>10 years old) (p=0.001). GM-CSF was found to be expressed in significantly lower percentage of children compared to adults (p=0.008). Conclusion: Our results implied that GM-CSF may have induces cell cycle arrest in adult ALL resulting in a lower percentage of S-phase fractions. This may contribute to the poorer prognosis in adults ALL because non-cycling blast are less sensitive to some chemotherapeutic drugs.